Career trinity : a roadmap to success. - See, Matthew Kuo Min. (2008)
We uncover the vital linkages between Career Anchors, Career Self-Management (CSM) Behaviors and Person-Job Fit. We focus on 3 Career Anchors (Entrepreneurial / Creativity, Service / Dedication and Lifestyle) in this study based on their increasing trends, popularity and their vital implications as noted by Edgar Schien.